Transition vers une économie bleue au Togo : apport de la recherche maritime et des infrastructures de recherche - Laré Batouth Penn (VertigO)
The development of the blue economy in Togo inevitably involves mastering knowledge of the maritime sector. However, we note that the mobilization of knowledge in this area is characterized by enormous challenges in terms of research and research infrastructures. This research, by combining documentary analysis and in-depth individual interviews with 65 resource people involved in State action at sea, aims to highlight the contribution of maritime research and research infrastructures in the promotion of the blue economy in Togo. The results of the study indicate that the country has a deficit in scientific knowledge and in terms of research infrastructures in the maritime, which would be sector capable of guiding public action in the formulation of decisions.